Supporting Awareness for Augmenting Participation in Collaborative Learning Hiroaki Ogata and Yoneo Yano. - Ogata, Hiroaki (Distributed by ERIC Clearinghouse, 1998)
This paper describes Coconuts (Concurrent Collaborative Learning Environment Supported by Awareness), a proposed module of Sharlok (Sharing, Linking and Looking-for Knowledge), an open-ended and collaborative learning environment that integrates a knowledge building tool with a collaborative interface tool. Coconuts was developed in order to support knowledge awareness (KA) during collaborative learning with Sharlok. Topics discussed include: collaborative learning in an open group, including an open-ended collaborative learning environment, the time dimension of open-ended collaborative learning, and the taxonomy of participation; an overview of Sharlok as a personal and collaborative learning environment; an overview of KA; and an overview of Coconuts, including features, system configuration, and the user interface. Results of an evaluation of Coconuts, in which nine master course students used Sharlok for 4 hours--2 hours unsupported by Coconuts and 2 hours supported by Coconuts--are presented. It is concluded that provision of awareness facilitates participation in multiple and concurrent collaboration and reduces wasteful formal participation, and that informal communication activates collaboration. A table categorizes collaborative learning in a closed versus open group, and five figures present a diagram of open-ended collaboration, the participation form of concurrent collaboration, the system configuration, screens of Coconuts in Sharlok, and frequency of participation results. Contains 12 references. (DLS)